2015
DOI: 10.1680/muen.14.00015
|View full text |Cite
|
Sign up to set email alerts
|

Street works and vision impairment: improving signing and guarding

Abstract: 2 3A design research project was conducted in London to investigate the issues experienced by people with vision impairment around street works and to generate and evaluate improvements to the manner in which street works are signed and guarded. A qualitative, ethnographic approach was taken to achieve a multifaceted understanding of street works equipment and its operation. A small sample of pedestrians with a range of vision impairment was observed interacting with a range of street works. Participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In addition to the current navigational methods, the visually impaired would like to see information about their environment such as lampposts, trees and other obstacles in the public space [2]. Atkins et al showed that beacons can be used to supply ad hoc information about a nearby obstacle in the environment where GPS cannot [5]. Havik et al developed a protocol for instructions supplied by RFID beacons [6], dictating the supply of detailed information about the environment, important landmarks and information about the next navigation point.…”
Section: Related Workmentioning
confidence: 99%
“…In addition to the current navigational methods, the visually impaired would like to see information about their environment such as lampposts, trees and other obstacles in the public space [2]. Atkins et al showed that beacons can be used to supply ad hoc information about a nearby obstacle in the environment where GPS cannot [5]. Havik et al developed a protocol for instructions supplied by RFID beacons [6], dictating the supply of detailed information about the environment, important landmarks and information about the next navigation point.…”
Section: Related Workmentioning
confidence: 99%
“…In their paper, Atkin et al (2015) trial modified signing and guarding arrangements with a range of visually impaired individuals to assess the degree to which their comfort can be improved when negotiating temporary traffic management arrangements for streetworks. A key finding is that individuals respond differently to cues and so information should be communicated in advance a variety of ways.…”
mentioning
confidence: 99%